ANALYSIS OF CONSUMER ATTITUDES AND PREFERENCES TOWARDS ORNAMENTAL PLANTS IN KARANGANDONG VILLAGE DRIYOREJO DISTRICT GRESIK REGENCY - Arfiana Dita Arum Sari; Teguh Soedarto; Prasmita Dian Wijayati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Ornamental plants are greenery with considerable potential for development in Indonesia. The plethora of ornamental plant sellers leads consumers to carefully choose attributes that stand out in meeting their desired attitudes and preferences. This research aims to analyze the decision-making process for purchasing ornamental plants, consumer attitudes toward ornamental plant attributes, and the attribute combinations that constitute consumer preferences for ornamental plants. The data collection method involves purposive sampling with 100 respondents. The analysis methods encompass descriptive analysis, Multi-Attribute Fishbein analysis, and Conjoint analysis. The research findings reveal the decision-making process for purchasing ornamental plants, including recognizing the need to beautify a room/home, seeking information from family, evaluating alternative attributes such as price, making planned purchasing decisions, and buying different types of ornamental plants. Post-purchase behavior includes satisfied consumers, a willingness to make repeat purchases, and spreading information about ornamental plants. The overall consumer attitude toward ornamental plants (Ao total) is positive. Consumer preferences for ornamental plants, based on utility values and attribute levels, prioritize plant price (Rp. 100,000 – Rp. 300,000), plant size (60 – 100 cm), seller service (empathy), plant pot (ceramic/porcelain), and plant type (ornamental leafy plants). Keywords: Attitude, Preference, Consumer, Ornamental plants